Curcuma aeruginosa, a novel botanically derived 5α-reductase inhibitor in the treatment of male-pattern baldness: a multicenter, randomized, double-blind, placebo-controlled study - Pumthong, Ganniga; Asawanonda, Pravit; Varothai, Supenya; Jariyasethavong, Vorapicha; Triwongwaranat, Daranporn; Suthipinittharm, Puan; Ingkaninan, Kornkanok; Leelapornpisit, Pimporn; Waranuch, Neti (The Journal of dermatological treatment, 2012)
Abstract Background: Several botanically derived agents are available for the treatment of male-pattern baldness. Objective: The aim of this study was to evaluate the efficacy of 5% hexane extract of Curcuma aeruginosa, a botanically derived inhibitor of 5α-reductase and 5% minoxidil in the treatment of androgenetic alopecia. Methods: Eighty-seven men with androgenetic alopecia (AGA) were randomized to receive 5% Curcuma aeruginosa, 5% minoxidil, combination formulation (5% hexane extract of Curcuma aeruginosa + 5% minoxidil) or placebo, twice daily for 6 months. Efficacy was assessed by target area hair count, global photographic review as well as patients' subjective assessments of hair regrowth and hair shedding. Results: There were statistically significant improvements in global photographic review (p < 0.001), subjects' overall assessments of hair regrowth (p = 0.008), and hair shedding (p = 0.004) when the combination formulation was compared with placebo. Similarly, treatment with 5% minoxidil and 5% C. aeruginosa extract also led to some degrees of hair regrowth. There were no serious adverse events during and after the study. Conclusion: In men with hair loss in the vertex area of the scalp, the combination of 5% hexane extract of C. aeruginosa and 5% minoxidil slowed hair loss and increased hair growth.